Validation of an educational technology: Manual for clinical management of breastfeeding in primary care (Research, Society and Development, 2021)
The evidence of the impact of breastfeeding goes far beyond the health benefits to mothers and their babies. Primary care plays a key role in providing trained and updated professionals to encourage this practice. The problem of this research is: How can a manual to guide nurses in the management of breastfeeding in primary care be validated? The objective was to validate a manual for clinical management of breastfeeding in primary care in Marabá. This is an applied experimental research of educational technology to validate the content of a manual for clinical management of breastfeeding to be used by nurses in primary care. The Cronbach's alpha calculation was used to investigate the consistency of the judges' responses through the variances between the scores of the questions presented. To determine the content validation of the manual, the CVI (content validation index) was used to calculate the concordances between the judges' responses. The Manual for Clinical Management of Breastfeeding in Primary Care in Marabá was structured in 16 chapters. At validation it presented Cronbach's alpha 0.86 with the objective of verifying the consistency of the form answered by the expert judges. The manual was categorized as validated in terms of relevance with a CVI variation of 0.91, with an approval rate of 96.9%. The manual was considered validated for use, being a technology of great usefulness and applicability in clinical practice of assistance to the mother-child pair, from prenatal to postpartum.